Perbandingan Kualitas Citra CT-Scan Kepala Pada Kasus Trauma Dengan Variasi Increment Di Rumah Sakit Balimed - Zulvania Do Rego Jesus; I Putu Eka Juliantara; I Kadek Sukadana (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Trauma is emotional and psychological stress in general due to unpleasant events or experiences related to violence. The word trauma can also be used to refer to events that cause excessive stress. An event can be called traumatic if the event causes extreme stress and exceeds the individual's ability to cope. The results of research related to variations in reconstruction increments in trauma cases show that the optimal increment reconstruction value on CT scan trauma head case trauma value increment reconstruction 2,5mm. Type study is quantitative with an experimental approach to analysis Quality information Citra Ct-Scan head with variations iincrement case trauma, with variations of 0,7mm, 0,9mm. Data collection was carried out in August-September 2023 at Balimed Regional Hospital. The author took examination dataas many as 10 patients. Research results from uji normality test on an clinical CT scan of the head in trauma cases use variations increments reconstruction 0,7mm, 0,9mm, can be seen that the mean increment value 0,7 mm produces a mean of 38,56 in the Ventricle-GM area, 15, 13 in the WM-GM area. And the mean increment value 0,9mm produces a mean of 19,88 in the ventricle-GM area, 7,1 in the WM-GM area. From the normality test on CT scan of the head in trauma cases using increment variations reconstruction 0,7mm, 0,9mm, it illustrates the image quality of the 2 increment variations, namely the increment variation value of 0,7 mm has the highest CNR value, namely a mean of 38, 56 in the ventricular-GM area, in the WM-GM area it was 15,13. Meanwhile, the increment variation value 0,9 mm produces 19.88 in the ventricular-GM area, in the WM-GM area 7,1. So this shows that an increment variation 0,7mm is the most optimal increment variation in improving the image quality of a CT scan of the head in trauma cases